X- and gamma rays cross sections and nuclear shielding performance of recycled cathode ray tube doping with high concentrations of Na2CO3 - Al-Buriahi, M. S.; Alzahrani, Jamila S.; Basha, Beriham; Tonguc, B. T.; Alrowaili, Z. A.; Sriwunkum, Chahkrit; Olarinoye, I. O. (Pergamon-Elsevier Science Ltd, 2024)
In an attempt to mitigate the increasing number of waste Cathod Ray Tube (CRT) glass in the environment, provide a safe, cheaper, and environmentally attractive recycling route for the glasses, and provide an alternative material for gamma radiation absorption applications, this study investigated the influence of adding Na2CO3 on the density, and gamma photon-absorbing prowess of CRT glass. Using the powder metallurgy process, CRT-NCx glasses consisting of CRT glass powder mixed with two distinct weight concentrations (20% (CRT-NC20 and 40% (CRT-NC40)) of Na2CO3 powder were prepared. The mass attenuation coefficients (mu/rho) of the prepared glasses were obtained using FLUKA simulations for 15 keV-15 MeV photons. The density of CRT, CRT-NC20, and CRTNC40 were 3.117 g/cm3, 2.987 g/cm3, and 2.894 g/cm3, respectively. The range of mu/rho for CRT, CRT-NC20, and CRT-NC40 corresponded to 0.0326-45.5236 cm2/g, 0.030-35.0662 cm2/g, and 0.0278-26.9813 cm2/g, respectively. The half-value layer and mean free path was found to vary within the range 0.005-6.822 cm and 0.007-9.842 cm for CRT; 0.007-7.748 cm and 0.010-11.178 cm for CRT-NC20; and 0.009-8.633 cm and 0.013-12.455 cm for CRT-NC40. The minimum and maximum values of mu en rho were 0.0216 and 37.7566 cm2/g for CRT, 0.0202 and 29.1167 cm2/g for CRT-NC20, and 0.01921 and 22.4430 cm2/g for CRT-NC40. CRT-rich glass showed higher radiation absorbed doses for the same beam energy and glass thickness. Na2CO3-rich glasses had lower buildup factors BFs, hence preferable in broad beam transmission scenarios. The investigated CRT-NCx glasses are more attractive for radiation protection functions in contrast to some well-known radiation shielding materials considering their lower mean free paths. The present glass system provides and alternative and effective gamma radiation shield, and also proffers a way of upcycling waste CRT glasses.
Keywords: Nuclear shielding; Radiation; Gamma; CRT recycled composites; FLUKA